Customer Experience and Facilities to encourage Revisit Intention with Customer Satisfaction as an intervening variable at the Old Town tourist attraction in Surabaya - Alfinatur Rosyida; Endah Budiarti (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research aims to prove and analyze the influence of Customer experience and Facilitiesin influencing interest in returning to visit with Customer Satisfaction as an intervening variable at the Old Town tourist attraction in Surabaya. This type of research is causal-explanatory the population is visitors to the Old Town in Surabaya. The sampling method uses Accidental Sampling which is a group of Non-Probability Sampling. The data collection method uses a questionnaire involving 100 respondents and Smart PLS 4 as the analysis tool. Customer satisfaction has a positive and significant impact on customer satisfaction, facilities have a positive and significant impact on customer satisfaction, customer experience has a positive but not significant impact on customer satisfaction, facilities have a negative and insignificant impact on customer intention, and customer satisfaction has a positive and significant impact on customer satisfaction. Additionally, facilities have a significant impact on customer satisfaction through customer satisfaction, and customer experience has a significant impact on customer satisfaction through customer satisfaction.